Performans Ayam Broiler Strain Cobb dengan Penambahan Tepung Daun Pepaya (Carica papaya Linn) dalam Ransum - Maydasari Maydasari; Abrani Sulaiman; Muhammad Riyadhi (JURNAL PENELITIAN PETERNAKAN LAHAN BASAH, 2014)
The use of papaya leaf in order to improve the performance of poultry in general it is possible,it is because the enzyme papain which works to increase appetite in the presence of polyphenolsthat give a distinctive taste, in addition to the enzyme papain also helps the absorption ofnutrients, amino acids settings, optimize work colon and remove toxins the body, so the immunesystem can be improved and the performance can be improved chicken anyway. Application ofpapaya leaf powder in broiler rations as a producer of meat has not been known. Broilerchickens which have experienced a lot of genetic modification, so as to take advantage of feedto produce meat in a relatively short time. In this study, researchers wanted to see how far theeffect of papaya leaf meal in broiler ration Cobb strain on feed consumption, body weight gain,feed conversion and weight gain end. This research method using a completely randomizeddesign (CRD) with 5 treatments and 4 replications which consists of 4 hens each replication,thus cobb broiler strains used as many as 80 tails. This research is the treatment rate ofaddition of papaya leaf meal in the ration consisting of: without the addition of papaya leaf powder (control, P0), the addition of 1.5% papaya leaf powder (P1), 3% (P2), 4,5% (P3), 6%(P4). Results of this study indicate that the addition of papaya leaf meal rations did notsignificantly affect feed intake, weight gain, feed conversion and weight gain end. But the bestindividual treatment groups to improve the performance of broiler chickens is at P1 treatmentby 1.5% due to increased feed intake, weight gain and final body weight, and can lower feedconversion, although not statistically significant.